Tariff-Tax Reforms in Large Economies - Tervala, Juha (IMF Working Papers; Working Paper ;, 2012)
This paper studies tariff-tax reforms in a calibrated two-region global New Keynesian model composed of a developing and an advanced region. In our baseline calibration, a revenue-neutral reform that lowers tariffs in developing countries can reduce domestic welfare. The reason is that the increase in developing countries welfare due to higher output is dominated by the welfare losses stemming from the deterioration of the terms of trade. On the other hand, the reform increases output and welfare in the advanced countries and in the world as a whole. The effects that we highlight have not been studied in previous contributions to the literature, which typically looks at tariff-tax reforms using a small open economy framework. Nominal rigidities have important implications for adjustment dynamics in our model. In the case of a "point-for-point" reform, for example, price stickiness implies that the international dynamics of output is reversed compared to a revenue neutral reform.